If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(h + 67) = -32 Reorder the terms: 8(67 + h) = -32 (67 * 8 + h * 8) = -32 (536 + 8h) = -32 Solving 536 + 8h = -32 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-536' to each side of the equation. 536 + -536 + 8h = -32 + -536 Combine like terms: 536 + -536 = 0 0 + 8h = -32 + -536 8h = -32 + -536 Combine like terms: -32 + -536 = -568 8h = -568 Divide each side by '8'. h = -71 Simplifying h = -71
| .6666(x+4)=8 | | 12a-6a^2=-48 | | 12a-6a^2=48 | | 4x+8x+40=304 | | 2x-16=24x+27 | | (2w+3)(8+w)=0 | | -8(u-86)+15=-65 | | p=h+5 | | 19=3(n+2)+1 | | (2x-3)=(x+16) | | 15x-2x+3=10 | | 3p+8-7p= | | -7(5x+5)+4x=3x | | 7y-x=9 | | .024a-8=.224a+2 | | 3(m-8)+-2=8 | | 6x+35=8x+15 | | 8t+2m=w-8 | | -22+t=36 | | -4(2t+2)=-32 | | -4(-6x+1)-3x=1 | | 25z-15=6z-14 | | .03x-3.9=.66 | | 7x+3x=5x+50 | | 8x+8-6x=-6 | | 25z-15=6z-24 | | 4=2(g-11)-2 | | (-7p)3= | | 2=7x-26 | | 15-g=6 | | -6+3(-8x+1)=15 | | 3(f-8)=-24 |